An investigation of the relationship between the performance and management practices of health facilities under a performance-based financing scheme in Nigeria. Issue 7 (17th May 2022) - Mabuchi, Shunsuke; Alonge, Olakunle; Tsugawa, Yusuke; Bennett, Sara
Abstract: Whereas the effect of performance-based financing (PBF) on improving the quantity and quality of health services has been established, little is known about what matters for health facilities to improve performance under a PBF scheme. This study examined the associations between management practices and the performance of primary healthcare centres (PHCCs) under a PBF scheme in Nigeria. This study utilized longitudinal data on monthly institutional deliveries and outpatient visits collected between December 2011 and March 2016 from 111 randomly selected PHCCs in Adamawa, Ondo and Nasarawa states of Nigeria. A management practices scorecard, based on a health facility survey conducted in April/May 2016, was used to derive management practices scores for the 111 PHCCs. The management practices examined included activities to recruit and retain clients, staff's attention to performance targets, listening and responding to client feedback, teamwork building and addressing low-performing staff. A multilevel, multilinear regression model was used to investigate the associations between health facility performance (monthly number of institutional deliveries and outpatient visits) and management practices at the PHCCs, adjusting for key control variables (number of skilled health workers, the size of PHCC catchment population, PHCC quality score, seasonality and states). Following PBF introduction, PHCCs with medium management scores had 0.42 (95% CI 0.18–0.65; P  < 0.001) and 9.93 (95% CI 6.15–13.71; P  < 0.001) higher monthly improvement rates for institutional delivery and outpatient visits, respectively, compared to the PHCCs with low management scores. Also, the PHCCs with high management scores had 0.49 (95% CI 0.28–0.70; P  < 0.001) and 5.10 (95% CI 1.76–8.44; P  < 0.003) higher monthly improvement rates for institutional delivery and outpatient visits compared to the PHCCs with low management scores. These findings suggest the importance of management practices in facilitating the effect of PBF on health facility performance and the need to strengthen PHCC management practices in low- and middle-income countries.